Pelaksanaan Maghrib Mengaji dalam Meningkatkan Keagamaan untuk Anak-Anak di Desa Kwala Mencirim - Fauziyah Syaputri Batubara; Kinanti Erdisyah Yusuf; Chintia Paramita Tarigan; Venny Dwita Sari; King Abdul Aziz Nasution; Ammamiarihta Ammamiarihta (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
The research was conducted with the aim of finding out the implementation of Maghrib Koran recitation in Kwala Mencirim village. The research method used in this research is descriptive qualitative using interview, documentation and observation techniques. This activity is one of the activities designed by Mathematics-2 Education students and students with the aim of increasing the religious beliefs of children in Kwala village to characterize and revive the children's enthusiasm for reciting the Koran after Maghrib. Because this activity has almost never been carried out at the Ainul Yaqin mosque (Kwala Mencirim Emplasm).